2007
DOI: 10.1002/app.25971
|View full text |Cite
|
Sign up to set email alerts
|

Properties of nanocomposites based on maleate‐vinyl ether donor—acceptor UV‐curable systems

Abstract: UV-curable nanocomposites based on donor-acceptor crosslinking chemistry were prepared containing organically modified montmorillonites. The coatings were characterized for thermal, mechanical, and morphological properties. X-ray diffraction and transmission electron microscopy showed that nanocomposites were formed in all samples. Results showed that an increase in the percentage of clay caused an increased modulus and glass-transition temperature. It was also seen that tensile modulus showed dramatic improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…The lower molecular weight reactive diluent and oligomers may more easily diffuse through the system leading to increased conversion. Similar trends regarding increased conversion with the introduction of clay has been reported in other UV‐curable nanocomposite systems 33, 38, 44…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The lower molecular weight reactive diluent and oligomers may more easily diffuse through the system leading to increased conversion. Similar trends regarding increased conversion with the introduction of clay has been reported in other UV‐curable nanocomposite systems 33, 38, 44…”
Section: Resultssupporting
confidence: 84%
“…In previous studies, we reported the development of UV‐curable coatings and polymer/clay nanocomposites based on the nonacrylate technology of donor‐acceptor chemistry 37, 38. Sonication was used to disperse the clay and monomers before photocopolymerization, and the resulting nanocomposite morphology was classified as intercalated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] However, the copolymers typically have low molecular weight and are mainly used as drug carriers, coatings, and so forth. [35][36][37][38][39] Monovinyl alkyl ethers as typical electron donors are readily to react with electron acceptors, like dialkyl maleates, to produce charge-transfer complex. Very recently, we reported the radical alternating copolymerization of vinyl hydroxyalkyl ethers with 1,2-disubstituted dialkyl maleates.…”
Section: Introductionmentioning
confidence: 99%
“…Nonconjugated electron‐rich monovinyl alkyl ether monomers are available in a wide range of substituents and multifunctionalities, which offer the corresponding homopolymers and copolymers a greater freedom in tuning their properties 32–34 . However, the copolymers typically have low molecular weight and are mainly used as drug carriers, coatings, and so forth 35–39 . Monovinyl alkyl ethers as typical electron donors are readily to react with electron acceptors, like dialkyl maleates, to produce charge‐transfer complex.…”
Section: Introductionmentioning
confidence: 99%